The MBR book principles and applications of membrane bioreactors for water and wastewater treatment - Judd, Simon (Butterworth-Heinemann, 2010)
A Membrane BioReactor (MBR) is the combination of a membrane process (e.g. microfiltration/ ultrafiltration) with a suspended growth bioreactor. When used with domestic wastewater, MBR processes can produce effluent of high enough quality to be discharged to waterways, or to be reclaimed for urban irrigation. Other advantages of MBRs over conventional processes include small footprint, easy retrofit and upgrade of old wastewater treatment plants. The MBR Book covers all important aspects of Membrane BioReactors in water and waste water treatment, from the fundamentals of the processes via design principles to MBR technologies. Industrial case studies help interpret actual results and give pointers for best practice. Useful appendices provide data on commercial membranes and international membrane organizations.-The MBR book enables readers to: Understand the fundamental processes involved in membrane and biotreatment technologies Compare and contrast design options and work through sample calculations Review commercial MBR systems in terms of specific applications Learn from case studies involving domestic and industrial effluent treatment and recycling Analyze process design, operation, performance and maintenance to draw conclusions appropriate to their requirements New to the second edition: 45% more content than the first edition. Over 120 contributors from the academic research and municipal/industrial practitioner communities. Review of MBR status in ten countries. Expanded section on anaerobic MBRs, micropollutant fate and hybrid systems. Simplified design methodology, with biokinetics for dynamic modelling and cost benefit analysis. Expanded operation and maintenance section, informed by expert panel of practitioners offering more than 40 years combined experience.-Over 40 MBR membrane products described, with most of the technical specifications provided. Over 50 case studies provided, including key design, performance, and operation and maintenance data in almost all cases. Membrane Bioreactors are a major growth area in the water and waste water treatment industries Internationally-known author, one of the leading senior experts in MBR research Principles and practice, backed by industrial case studies.